2021
DOI: 10.1080/10942912.2021.1873361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lemon water vapor extract (LWAE) from lemon byproducts on the physiological activity and quality of lemon fermented products

Abstract: The byproducts of lemon juice have always constituted an environmental issue. In this study, the byproducts extracted to lemon water vapor extract (LWAE) by distilled, which was added to lemon fermented products (LFP) to evaluate its effect on its quality and bioactivity. Based on the gas chromatography-mass spectrometry results, the main component of the LWAE was D-limonene (>41%). After added 5% LWAE the amount of D-limonene in non-sterilized lemon fermented product (NLFP) increased from 10.1% to 20.9%, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Fermented lemons contain bountiful bioactive components that beneft human health [15], and can improve the nutrition and efectiveness of food [32] and antioxidant activity and promote the decomposition of plant cell walls, which helps to release or produce various antioxidants. Compounds with potential health benefts, such as reducing the probability of cardiovascular and chronic diseases [33], sugar, yeast, or lactic acid bacteria, are added to the raw materials for fermentation, thereby activating various enzymes in the raw materials and producing various functional substances, while the nutrients contained in the raw materials are converted into a form that is easier to digest and absorb [34], fermentation can increase the phenolic content and antioxidant activity of plants [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermented lemons contain bountiful bioactive components that beneft human health [15], and can improve the nutrition and efectiveness of food [32] and antioxidant activity and promote the decomposition of plant cell walls, which helps to release or produce various antioxidants. Compounds with potential health benefts, such as reducing the probability of cardiovascular and chronic diseases [33], sugar, yeast, or lactic acid bacteria, are added to the raw materials for fermentation, thereby activating various enzymes in the raw materials and producing various functional substances, while the nutrients contained in the raw materials are converted into a form that is easier to digest and absorb [34], fermentation can increase the phenolic content and antioxidant activity of plants [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lemon peel and pomace are often treated as waste and discarded. However, lemon peel contains numerous active compounds, including polyphenols, pectin, and favonoids [15]. In addition, lemon peel polyphenols are proposed to prevent weight gain, fat accumulation, and hyperlipidemia [16].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has found that the content of limonene in lemon juice is 6.13%. After fermentation, LFP has 10.55% limonene content [ 22 ]. Hence, limonene content can be increased by 4.42% after fermentation with Lactobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it could maintain mitochondrial integrity and reduce oxidative stress damage by increasing the mitochondrial membrane potential [ 21 ]. In addition, LFP contains excellent physiological and bioactive compounds, such as polyphenols, vitamin C, flavonoid, and limonene [ 22 ]. Previous studies show that polyphenols, flavonoids, and limonene have anti-obesity effects [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%